Implementasi Hukum Pidana terkait Maraknya Praktek Prostitusi Wanita dan Anak Dibawah Umur di Negara Indonesia - Galuh Tiara Cindy Aulia (Bhirawa Law Journal, 2022)
The phenomenon of prostitution is a form of crime that is very difficult to deal withand this type of crime is mostly supported by economic factors in people’s lives, where in society itself until now, prostitution has not been stopped, as well as a threat to sex morality, household life, health and welfare of women. The practice of sex transactions occurs not only with prostitutes from among adults, but also teenagers. Therefore, the Government should be more active in finding solutions to problems like this. This study uses normative juridical research and the results of this study state that there are several factors that make a person enter the world of prostitution, including; economic factors, lifestyle and frustration. Then the government’s role in dealing with prostitution in Indonesia has been carried out using two methods, namely the elimination method and the registration method.